Challenges in application of bioanalytical method on different populations and effect of population on PK. (December 2014) - Kale, Prashant; Shukla, Manoj; Soni, Gunjan; Patel, Ronak; Gupta, Shailendra
Prashant Kale has 22 years of immense experience in the analytical and bioanalytical domain. He is Senior Vice President, Bioequivalence Operations of Lambda Therapeutic Research, India which includes Bioanalytical, Clinics, Clinical data management, Pharmacokinetics and Biostatistics, Protocol writing, Clinical lab and Quality Assurance departments. He has been with Lambda for over 14 years. By qualification he is a M.Sc. and an MBA. Mr. Kale is responsible for the management, technical and administrative functions of the BE unit located at Ahmedabad and Mumbai, India. He is also responsible for leading the process of integration between bioanalytical laboratories and services offered by Lambda at global locations (India and Canada). Mr. Kale has faced several regulatory audits and inspections from leading regulatory bodies including but not limited to DCGI, USFDA, ANVISA, Health Canada, UK MHRA, Turkey MoH, WHO. There are many challenges involved in the application of bioanalytical method on different populations. This includes difference in equipment, material and environment across laboratories, variations in the matrix characteristics in different populations, differences in techniques between analysts such as sample processing and handling and others. Additionally, there is variability in the PK of a drug in different populations. This article shows the effect of different populations on validated bioanalytical method and on the PK of a drug. Hence, the bioanalytical method developed and validated for a specific population may need required modification when applied to another population. Critical consideration of all such aspects is the key to successful implementation of a validated method on different populations.